Pengaruh Kepatuhan Wajib Pajak Orang Pribadi Berdasarkan Theory Planned Of Behaviour (TPB) - Hurian Kamela (Journal of Applied Accounting and Taxation, 2020)
There must be an awareness of the public regarding compliance in paying taxes. Tax is a state asset that is collected by the state for the common interest. The role of society in paying taxes must be accompanied by internal (within) the individual itself because there are still limited people who know that taxes are crucial. This study aims to link the effect of individual taxpayer compliance based on the "Theory of Planned Behavior" because this theory is a theory that can measure the internal thinking of taxpayers. This study uses primary data collected through a questionnaire using linear regression analysis. The sample used is a sample (people) of 100 taxpayers using measurements random sampling (people who are in the tax office) 1 month (November 2015). The study results found that the variable attitudes toward behavior, subjective norms and perceptual behavior control were positive influences. That explains a need for awareness of taxpayer compliance to run appropriately, and income from tax payments can increase.